EFFECT OF HERBAL TOOTHPASTE CONTAINING NEEM LEAVES EXTRACT (AZADIRACHTA INDICA) AGAINST GINGIVITIS: A CLINICAL STUDY - SUGIARTA, AMELIA PRISCILLA; LESSANG, ROBERT; NATALINA (International Journal of Applied Pharmaceutics, 2019)
Objective: Neem leaves are known to have antibacterial, anti-inflammatory, antifungal, antiseptic, antitumor, antihyperglycemic, antiulcer, and antiviral effects. In addition, they can reduce the counts of plaque-forming bacteria in the oral cavity. This study aimed to evaluate the effect of an herbal toothpaste containing neem leaves extract against gingivitis. Methods: A total of 40 subjects were divided into two groups (n=20 each): Experimental and control. Those in the test group were instructed to brush their teeth twice a day for 7 days with neem leaves extract toothpaste, whereas the control group subjects were asked to continue with the non-herbal paste they used for tooth brushing. Plaque index (PI) and papillary bleeding index (PBI) were measured on day 0 and day 7. Results: Significant reductions in PI and PBI were noted between the test and control groups. Conclusion: The findings of this clinical study provide evidence that neem leaf extracts are effective in reducing gingivitis.